Analysis of The Effect of Ice Breaking on Interpersonal Development of Early Childhood - Saniy, Mawari Melati Almas; Hartono, Hartono; Sarwi, Sarwi (Universitas Negeri Semarang, 2021)
Early childhood education is essentially education that is held to facilitate the growth and development of children as a whole or emphasize the development of all aspects of the child's personality, especially interpersonal aspects. The purpose of this study is to analyze the effect of ice breaking on the interpersonal development of early childhood. This study was used a quantitative approach or quasi-experimental research designs. The data collection method was used observation and documentation. Data analysis techniques was used the t-test with the help of SPSS 23.0 for windows. The results showed that there were differences in interpersonal abilities of young children before and after ice-breaking activities. The pretest value of interpersonal aspects of early childhood in the control and the experimental class has a probability value of 0.000 > 0.05. While the post - test interpersonal aspects of early childhood in the control class and the experimental class have a probability value of 0.000 < 0.05. Increased interpersonal aspects of early childhood before and after the ice-breaking activity around of 72.34%. It was concluded that the hypothesis was accepted that there was a significant increase in the development of interpersonal aspects of the age of 5-6 years through ice-breaking activities.